Quality Wafer Fiber Fraction from Sago Dregs with Various Types of Adhesives and Storage Times - Harahap, Anwar Efendi (Journal of Tropical Animal Science and Technology, 2024)
This study aims to determine the quality of nutrition in the form of wafer-shaped feed fiber fractions using different types of adhesives and storage times. This study used an experimental method using Factorial RAL. Factor A was storage time of 0, 7, and 14 days and factor B was tapioca adhesive, wheat flour and rice flour. The results showed that factor A (storage time) had a very significant effect (P<0.01) on the decrease in the content of neutral detergent fiber, acid detergent fiber, acid detergent lignin and hemicellulose. Furthermore, factor B addition of adhesive material also had a very significant effect (P<0.01) on the decrease in the content of neutral detergent fiber, acid detergent fiber, acid detergent lignin and hemicellulose. The conclusion of this study is that the addition of sago pulp content up to 30% can reduce the content of the complete ration wafer fiber fraction. The best treatment is the addition of sago pulp level, namely at 14 days of storage using tapioca flour as an adhesive can reduce the nutritional content in the form of neutral detergent fiber, acid detergent fiber and acid detergent lignin